The influence of social media on purchase intention, brand awareness, and brand loyalty: a focus on customers’ engagement with brands on the platforms - Nyatlo, Mmasetena Rahab (My University, 2018)
The internet has transformed the way people communicate, it has allowed people and brands to communicate beyond geographic and time restrictions. The internet has introduced with it social media, which is a new way that brands and customers communicate, share ideas and exchange information. These interactions have a weighty effect on marketing strategies, therefore social media marketing has become critical for businesses. Through these interactions brands can gauge customer’s attitudes towards the brand’s different offerings. Understanding customer attitudes is an important part to knowing the customers’ buying decision process. Currently new businesses in South Africa mostly fail within a few years of operating. Some of the reasons leading to failure include access to markets, poor marketing, and lack of funding. Social media is a channel which businesses can use to access markets and market their offering as these platforms boast large number of potential customers. These customers are every business’ most important asset and revenue source which assist SMEs in their growth. Therefore, SMEs need to understand how their engagement with customers influences their attitudes towards them as this contributes towards their growth. The purpose of this research is to evaluate customers’ attitudes by understanding how customer engagement with SMEs on social media influences brand loyalty, purchase intention, and brand awareness which will aid in venture growth and in turn economic growth. The study followed a quantitative and positivist method. A survey was distributed through email and social media platforms to existing and potential customers who have a presence on the platforms to collect data, and the study achieved a 38% response rate. The study revealed positive customer’s attitudes towards SMEs that operate on social media platforms. These findings contribute towards the knowledge of SME growth and social media
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, University of the Witwatersrand, 2018
Keywords: Consumer behavior; Social media--Economic aspects; Branding (Marketing)--South Africa; Customer relations; SDG-8: Decent work and economic growth